Food system diagnostics and policy implications: The Malawi case - Matchaya, Greenwell C.; Guthiga, Paul (2023)
Food systems are at the heart of Africa’s economic growth and development plan, Agenda 2063: The Africa We Want. Without ending hunger and improving the food and nutrition status of Africa’s population, the agenda’s first aspiration for a “prosperous Africa based on inclusive growth and sustainable development” cannot be effectively reached. To realize this aspiration, African countries need to progressively implement the seven Comprehensive Africa Agriculture Development Program (CAADP) Malabo commitments while having strategies to address wider food system challenges (AU 2023). The concept of a food system has various definitions, but for the purposes of this chapter, a food system is considered as a network of actors or players and their activities along the entire food value chain from inputs to production, distribution, and consumption. This aligns with the definition espoused by the Scientific Group of the UN Food Systems Summit (UNFSS), that food systems are constitutive of food actors and their interlinked activities from production all the way to consumption or utilization (von Braun et al. 2020).